Study of cases with perinatal mortality - Pancholi, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Perinatal loss is one of the most traumatic life events. It is indeed a great psychological and emotional shock to not only the mother and father but the entire family and society as a whole. The perinatal mortality rate (PMR) is an important indicator of the quality of obstetric care during pregnancy. Perinatal deaths result largely from obstetric complications that can be prevented with proper antenatal care and quality neonatal services. The study was aims to study the factors related with perinatal loss and its prevention in future pregnancy. Methods: It was a prospective analytical study. All patients with IUFD, stillbirths and early neonatal loss were studied. Postpartum both mother and father were counselled. Detailed history and thorough physical examination were conducted. Data was recorded and tabulated, observation made and compared with results of various studies. Results: The results showed that the incidence of IUFD was 3.7% and early neonatal death was 10.8% per total admissions. The perinatal mortality rate was 63.62 per 1000 live births. Perinatal mortality rate was inversely related to the number of antenatal visits taken by the patient. Lack of antenatal care results in perinatal deaths probably due to failure of early identification and management of maternal problems that impact negatively on perinatal outcome. Even in advanced economies with sophisticated diagnostic and monitoring equipment, lack of antenatal care categorizes a pregnant woman as a high-risk pregnancy. Conclusions: There is a need for awareness regarding importance of antenatal care and institutional delivery. Perinatal mortality is an important indicator of maternal care, health and nutrition. It also reflects the quality of Obstetric and Pediatric care available. Every effort must be made to reduce perinatal mortality.